On ultrafast x-ray scattering methods for magnetism - R. Plumley; S. R. Chitturi; C. Peng; T. A. Assefa; N. Burdet; L. Shen; Z. Chen; A. H. Reid; G. L. Dakovski; M. H. Seaberg; F. O’Dowd; S. A. Montoya; et al. (Advances in Physics: X)
With the introduction of x-ray free electron laser sources around the world, new scientific approaches for visualizing matter at fundamental length and time-scales have become possible. As it relates to magnetism and ‘magnetic-type’ systems, advanced scattering methods are being developed for studying ultrafast magnetic responses on the time-scales at which they occur. We describe three capabilities which have the potential to seed new directions in this area and presentoriginal results from each: pump-probe x-ray scattering with low energy excitation, x-ray photon fluctuation spectroscopy, and ultrafast diffuse x-ray scattering. By combining these experimental techniques with advanced modeling together with machine learning, we describe how the combination of these domains allows for a new understanding in the field of magnetism. Finally, we give an outlook for future areas of investigation and the newly developed instruments which will take us there.